A influência do alagamento apical na distribuição de tensões em canais radiculares curvos: análise de elementos finitos - Lang, Pauline Mastella (2013)
Localized irregularities in the canal walls are sities which concentrate stresses and make the stresses distribution occurs asymmetrically in the root structure during the filling phase. This asymmetric distribution of stresses may contribute to the generation of defects in the dentin, which can propagate in vertical root fracture (VRF). Thus, this study evaluated the influence of enlargement in the apical stress distribution in curved canals when a spreader digital was inserted against the canal walls using Finite Element Analysis (FEA). A basic three-dimensional geometric model of the mesiobuccal root (MV) of a Maxillary First Molar (1ºMM) with root canal curved and anatomical diameter 0.25 mm was confectioned with the program SolidWorks Simulation (Dassault Systèmes SolidWorks Corporation, France). Based on this basic model, four post-instrumentation geometric models were established to accommodate canal preparation performed with HERO 642 (Micromega, Besançon, France) instruments 30/.02 (IAF +1); 35/.02 (IAF +2); 40/.02 (IAF +3) and 45/.02 (IAF +4). In the program SolidWorks Simulation, the models were discretized in a finite number of elements united by their nodal points. To the models were attributed to mechanical properties of dentin that characterized their mechanical behavior. The models were fixed to the outer surface to limit the rotational and translational movements in all directions during the simulation. A load of 13 N was applied along the canal walls (mesial, distal, buccal and palatal) up to 3 mm of the apical foramen simulating the action of a spreader digital Nickel-Titanium (NiTi) B Dentsply Maillefer, Ballaigues, Switzerland). The results of AEF showed a better distribution of stresses as further enlargement was performed. The highest stress decreased distal and palatal walls of the canal because of the increased apical enlargement. The location of the highest value of stress changed in the buccal and palatal walls due to increased apical enlargement. Thus, it can be concluded that the enlargement apical improve the distribution of stresses in curved canals when a digital spreader is inserted against the walls of the canal.